2017
DOI: 10.1021/acs.chemmater.7b03061
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Phase Engineering of Niobium Diselenide

Abstract: With continuing miniaturization in semiconductor microelectronics, atomically thin materials are emerging as promising candidate materials for future ultra-scaled electronics. In particular, the layered transition metal dichalcogenides (TMDs) have attracted significant attention due to the variety of their electronic properties, depending on the type of transition metal and its coordination within the crystal. Here, we use low-temperature scanning tunneling microscopy (STM) for the structural and electronic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
52
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 70 publications
6
52
1
Order By: Relevance
“…S1. The sharp minima in the phonon dispersion of the single layer, located near the √ 13 × √ 13 region, support a recently observed 2H-1T structural transition [42,43].…”
supporting
confidence: 85%
See 1 more Smart Citation
“…S1. The sharp minima in the phonon dispersion of the single layer, located near the √ 13 × √ 13 region, support a recently observed 2H-1T structural transition [42,43].…”
supporting
confidence: 85%
“…Lack of inversion symmetry and van der Waals bonded layers may result in remarkably different behavior with respect to the bulk [39][40][41]. The 2H-1T crystal phase transition at the surface of NbSe 2 [42,43] (the 1T crystal phase is unstable in the bulk [44]), the occurrence of 4 × 4 [3,4] and/or a 2 × 2 [4] modulations, linked to a stripe phase, and the observation of distinct charge density wave structures, determining a factor for the incommensuration character [6], are just a few recent examples. A change from the 3×3 to the 4×4 modulation was previously predicted by ab-initio studies [20,48]; on the other hand, a recent study [5] showed that within a 3 × 3 modulation, uniaxial strain leads to a trigonal-stripe CDW stransition.…”
mentioning
confidence: 99%
“…Finally, we would like to point out that although here we elaborate the phase transition largely based on group‐6 TMDs, the same mechanisms actually can be adopted to understand the phase transition in other groups of TMDs …”
Section: In Situ Observation Of Phase Transitionmentioning
confidence: 99%
“…Not surprisingly, the ARPES data in the CDW phase are in stark disagreement with electronic structure calculations in the high symmetry 1TNbSe 2 phase [17]. Finally, and most interesting, Bischoff et al [18] recently showed that it is possible to transform the surface of exfoliated 2HNbSe 2 samples into a 1TNbSe 2 phase by applying STM bias pulse of 4V for 100 ms. The 1TNbSe 2 phase in the top layer is then (meta)stable at 77 K and displays the occurrence of the characteristic √ 13 × √ 13 R30 • reconstruction.…”
mentioning
confidence: 94%